2014
DOI: 10.2169/internalmedicine.53.1410
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and C Virus Infection is a Risk Factor for the Development of Cholangiocarcinoma

Abstract: Objective Chronic hepatitis B virus (HBV) and hepatitis C virus (HCV) infection may be involved in the development of cholangiocarcinoma. The prevalence of HBV and HCV infection was examined in patients with intrahepatic cholangiocarcinoma (ICC) and extrahepatic cholangiocarcinoma (ECC). Methods The levels of HBV surface antigens (HBsAg), antibodies against HBV core antigens (HBcAb) and hepatitis C virus antibodies (HCV-Ab) were determined in sera obtained from 145 consecutive patients (50 patients with ICC, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 14 publications
1
39
0
1
Order By: Relevance
“…In the current study, our findings demonstrated that 26.8% (26/97) of patients with ICC were HBsAg positive (group I), which is much higher than the incidence of patients with negative HBsAg (group II and group III). Our findings are consistent with recent studies in which the data suggested that seropositivity of HBsAg was one of the most important risk factors for HCC and that HBV infection is a possible risk factor for the development of cholangiocarcinoma [10,20,21].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, our findings demonstrated that 26.8% (26/97) of patients with ICC were HBsAg positive (group I), which is much higher than the incidence of patients with negative HBsAg (group II and group III). Our findings are consistent with recent studies in which the data suggested that seropositivity of HBsAg was one of the most important risk factors for HCC and that HBV infection is a possible risk factor for the development of cholangiocarcinoma [10,20,21].…”
Section: Discussionsupporting
confidence: 93%
“…One of our previous studies as well as several others suggested that HBV infection may be one of the reasons for the development of ICC [6,[9][10][11][12]. The impact of HBV infection on HCC has been studied extensively [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, liver cirrhosis and viral hepatitis B and C have been recognized as risk factors for cholangiocarcinoma, especially intrahepatic disease [50,51,52]. Viral hepatitis-associated cholangiocarcinogenesis is most probably linked to chronic inflammation and increased cell proliferation [53].…”
Section: Hepatitis B and Cmentioning
confidence: 99%
“…A total of 39 studies with CCA matched the inclusion criteria in this meta-analysis, including 21 studies [1131] for estimating the incidence rates of CCA, 14 studies [3245] for unadjusted OR, and 7 studies [32, 33, 36, 39, 41, 42, 44] for adjusted OR analysis (Tables 1 and 2). Among the 39 studies, 26 studies were for ICC, including 13 studies [1114, 16, 17, 19, 22, 23, 25, 26, 29, 31] for estimating the incidence rates of ICC, 11 studies [32, 3436, 3942, 44, 45, 47] for unadjusted OR analysis, and 7 studies [32, 35, 36, 39, 41, 42, 44] for adjusted OR analysis (Tables 3 and 4). Nine studies were for ECC, including 3 studies [11, 15, 20] for estimating the incidence rates of ECC, 5 studies [32, 35, 40, 43, 47] for unadjusted OR analysis, and 1 study [35] for adjusted OR analysis (Tables 4 and 5).…”
Section: Resultsmentioning
confidence: 99%